2017
DOI: 10.1111/bjhp.12289
|View full text |Cite
|
Sign up to set email alerts
|

‘It's when you're not doing too much you feel tired’: A qualitative exploration of fatigue in end‐stage kidney disease

Abstract: BackgroundFatigue is commonly experienced in end‐stage kidney disease (ESKD) patients. In order to develop patient‐centred psychosocial interventions to help patients manage fatigue symptoms, a more in‐depth understanding regarding the experience of fatigue is needed.ObjectiveThe objective of this study was to explore renal patients’ experiences of fatigue, across renal replacement therapy (RRT) modalities.MethodsTwenty‐five in‐depth semi‐structured interviews were conducted. Interviews were audio‐taped, trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 54 publications
4
27
0
4
Order By: Relevance
“…Twelve out of 15 participants described experiencing negative mood and in some cases clinically diagnosed depression and suicidal thoughts as a result of their condition/s, and eight reported experiencing anxiety and fear for the future. This complements and expands on earlier findings with predominantly older adults and/or amongst individuals with specific individual LTCs . Nine out of 15 participants made comparisons between their former ‘well’/’healthy’ self and their current ‘ill’/‘sick’ self, with longing for their past self and grieving lost parts of their identity (although it is important to note that this sub‐theme is only applicable to young adults diagnosed from birth/infancy, perhaps excluding for example congenital illnesses such as cystic fibrosis, where there is no prior period of ‘wellness’ or perceived ‘normality’).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Twelve out of 15 participants described experiencing negative mood and in some cases clinically diagnosed depression and suicidal thoughts as a result of their condition/s, and eight reported experiencing anxiety and fear for the future. This complements and expands on earlier findings with predominantly older adults and/or amongst individuals with specific individual LTCs . Nine out of 15 participants made comparisons between their former ‘well’/’healthy’ self and their current ‘ill’/‘sick’ self, with longing for their past self and grieving lost parts of their identity (although it is important to note that this sub‐theme is only applicable to young adults diagnosed from birth/infancy, perhaps excluding for example congenital illnesses such as cystic fibrosis, where there is no prior period of ‘wellness’ or perceived ‘normality’).…”
Section: Discussionsupporting
confidence: 63%
“…This also expands on previous research which has identified reaching acceptance of new/altered identities as important for mental health, and was also seen as a long and difficult process that required time and reflection (eg Refs). The other suggestions made by participants in the present study are less present in the existing literature, although some reference has previously been made to the value of positive thinking (eg Refs).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The role of damage beliefs in fatigue-related functional impairment was also evident in the crosssectional data (Chilcot et al, 2016). Believing that fatigue is a sign of damage appeared particularly salient to renal patients and has been previously reported in a qualitative study, where patients often struggled to dissociate fatigue from the experience of the illness and treatment (Picariello et al, 2017a(Picariello et al, , 2017. Believing that fatigue is a sign of damage appeared particularly salient to renal patients and has been previously reported in a qualitative study, where patients often struggled to dissociate fatigue from the experience of the illness and treatment (Picariello et al, 2017a(Picariello et al, , 2017.…”
Section: Discussionsupporting
confidence: 61%
“…The lack of debilitating symptoms may mean that people are less inclined to believe that they have CKD (Braun, Sood, Hogue, Lieberman, & CopleyMerriman, 2012;Picariello, Moss-Morris, Macdougall, & Chilcot, 2017a), and could reduce their engagement in self-management behaviours, particularly those related to lifestyle modifications. Providing support is therefore essential to assist people in knowing what CKD is, how to identify early symptoms, and how to take steps to manage their disease.…”
Section: 21mentioning
confidence: 99%